IMPROVING ENGLISH VOCABULARY ACQUISITION IN REMOTE AREAS - Priyono, Ilham; Aziza, Aziza (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
The Fun English at SDN 6 Tambak Ukir (FeaST) program was designed to enhance English vocabulary acquisition among elementary school students in 3T (underdeveloped, outermost, and frontier) areas. Implemented at SDN 6 Tambak Ukir, Situbondo, the program addressed the lack of English learning resources and specialized teachers by engaging university student tutors to facilitate interactive learning activities. The program was carried out in three phases: preparation, implementation, and evaluation. Activities included vocabulary games, reading exercises, and storytelling to encourage student participation. The results showed a significant improvement in students' English vocabulary and increased engagement in learning. Teachers also gained new teaching strategies to sustain the program beyond its initial implementation. However, challenges such as limited student attendance and varying language proficiency levels required adaptive teaching methods. The FeaST program demonstrates that structured intervention can enhance English language learning in remote schools. Further development and integration into the school curriculum are recommended to ensure long-term sustainability.